Genetic Variability for Early Growth Traits in Second Season Sunflower - Lamichhane, Jay Ram; Wojciechowski, Alexandre; Bourgeois, Clémentine; Debaeke, Philippe (Frontiers in Agronomy, 2022)
Sowing a second season crop following the harvest of a first crop (hereafter referred to as double cropping) is a practice that allows temporal diversification of cropping systems to increase land use efficiency and yield per unit area while improving ecosystem services. Sunflower is particularly suitable for double cropping, especially under the context of Southern Europe. However, planting sunflower in double cropping may result in poor establishment as the crop is very demanding in terms of seedbed preparations. In addition, most sunflower varieties available to date belong to late maturity groups (MGs), which were bred for conventional cropping. Planting these varieties in double cropping may further exacerbate the risk of crop establishment failure. Here, we perform laboratory and growth chamber phenotyping of 11 hybrid oilseed sunflower varieties with contrasting MGs and assess their field performance for two consecutive years (2020-2021). Under laboratory conditions, we found statistically significant effect of varieties on cardinal temperatures and water potential for germination. Under growth chamber conditions, the maximum heterotrophic growth of hypocotyl was higher (i. e. 85 mm) compared with that of radicle (i.e. 80 mm). The seedling mortality rates under soil aggregates ranged from 0 to 12%, depending on the size and spatial distribution of soil aggregates in the seedbed. Under field conditions, final rates of seed germination ranged from 87 to 98% and from 99 to 100%, while those of seedling emergence ranged from 58 to 87% and from 78 to 94%, in 2020 and 2021, respectively. The average final rates of post-emergence damage ranged from 13 to 44% and from 3 to 18% in 2020 and 2021, respectively. Bird damage was the main cause of pre- and post-emergence losses. We show that a good sunflower establishment in double cropping is possible under southwestern conditions of France provided that there is no water stress in the seedbed. An optimal seedbed moisture ensures a rapid crop emergence and limits pre-and post-emergence damage due to birds, by reducing the duration of the crop establishment phase, which is highly vulnerable to bird damage.